Finite (Hausdorff) dimension of plants and roots as indicator of ontogeny - Alonso, Juan M.; Alvarez, Juan Agustín; Vega Riveros, Cecilia; Pablo, Villagra (Revista de la Facultad de Ciencias Agrarias UNCuyo, 2019)
The architecture of plants responds to endogenous processes and to the influence of environmental factors. The allometric study of architecture has been a challenge for biology. We define a new finite (Hausdorff) dimension of plants, that considers both the aerial part and the roots, and compute examples. This new finite dimension was introduced recently and, in contrast to the classical Hausdorff dimension, is not zero on finite sets. We propose the finite dimension, as a function of time, as a "signature" of the plant or root. Our first results suggest that the signature is specific to each plant species and its growth period, and constitutes an objective metric that allows to study its ontogenesis in detail.